(untitled) (Iranian Journal of Kidney Diseases, 2010)
Hypertension in children is not as frequent as adults. In addition, most of the times, we encounter secondary hypertension rather than essential hypertension in children. This demands careful history taking, physical examination, and laboratory and imaging investigations to find the underlying cause. Here, a boy with tuberous sclerosis is reported who presented with hypertension and abdominal pain associated with bilateral renal cystic disease.